Multiple Representations in Dispelling Some Common Misunderstandings and Increasing the Clarity of Principles of Physics Taught at Secondary School Level - Piyatissa, Madawala Liyanage Shanaka; Johar, Md Gapar Md; Tarofder, Arun Kumar (Asian Journal of Contemporary Education, 2018)
In this study, it is expected to highlight some common illusions that can interfere with classroom teaching of physics at secondary school. Cases cited here surfaced as useful by-products while some experimental teaching sessions were being conducted with grades 10 and 11 students in three government schools in a suburb of Western province in Sri Lanka. The main purpose of that exercise was to test the efficacy of visual-perceptual approach to teaching on some physics lessons, namely, kinematics, Newton’s laws of motion and equilibrium of forces, turning effect of forces etc. It has become necessary to keep an open dialog with students and to get their active participation in the teaching / learning process in order to prepare a suitable visual-perpetual assessment tool to measure their performance at the end of the teaching exercise. This teaching sessions spans for about 15 hours after school and spread over three months (each period being 40 minutes duration). These classes were held with the help of the respective science teachers of the school. The problematic cases for the students that will be discussed in detail later were successfully tackled by employing appropriate lesson specific visualization objects in conjunction with existing traditional methods of teaching. Sometimes more than one visualization mode (external representations) had to be used to facilitate better understanding of the same principle. End result seemed satisfactory in terms of marks scored for the visual-perceptual assessment tool and, student and teacher interviews.